Generalized Equilibrium Problems Related to Ky Fan Inequalities - Ionel Rovenţa (Abstract and Applied Analysis)
We study a generalized equilibrium problem by using a nonsymmetric extension of Ky Fan’s inequality. As an application, we present a fixed point type algorithm inspired by a model from Tada and Takahashi (2007).